Cement production technology : principles and practice - Chatterjee, Anjan Kumar; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This multidisciplinary title on cement production technology covers the entire process spectrum of cement production, starting from extraction and winning of natural raw materials to the finished products including the environmental impacts and research trends.
chapter one Basics of mineral resources for cement production / Anjan Kumar Chatterjee -- chapter two Raw mix proportioning, processing, and burnability assessment / Anjan Kumar Chatterjee -- chapter three Fuels commonly in use for clinker production / Anjan Kumar Chatterjee -- chapter four Alternative fuels and raw materials / Anjan Kumar Chatterjee -- chapter five Pyroprocessing and clinker cooling / Anjan Kumar Chatterjee -- chapter six Clinker grinding and cement making / Anjan Kumar Chatterjee -- chapter seven Composition and properties of Portland cements / Anjan Kumar Chatterjee -- chapter eight Advances in plant-based quality control practice / Anjan Kumar Chatterjee -- chapter nine Environmental mitigation and pollution control technologies / Anjan Kumar Chatterjee -- chapter ten Trends of research and development in cement manufacture and application / Anjan Kumar Chatterjee -- chapter eleven Global and regional growth trends in cement production / Anjan Kumar Chatterjee -- chapter twelve Epilogue / Anjan Kumar Chatterjee.
Keywords: Cement industries -- Technological innovations; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY & ENGINEERING / Material Science; TECHNOLOGY & ENGINEERING / Structural